Deletion of the huntingtin polyglutamine stretch enhances neuronal autophagy and longevity in mice. - Shuqiu Zheng; Erin B D Clabough; Sovan Sarkar; Marie Futter; David C Rubinsztein; Scott O Zeitlin (PLoS Genetics)
Expansion of a stretch of polyglutamine in huntingtin (htt), the protein product of the IT15 gene, causes Huntington's disease (HD). Previous investigations into the role of the polyglutamine stretch (polyQ) in htt function have suggested that its length may modulate a normal htt function involved in regulating energy homeostasis. Here we show that expression of full-length htt lacking its polyglutamine stretch (DeltaQ-htt) in a knockin mouse model for HD (Hdh(140Q/DeltaQ)), reduces significantly neuropil mutant htt aggregates, ameliorates motor/behavioral deficits, and extends lifespan in comparison to the HD model mice (Hdh(140Q/+)). The rescue of HD model phenotypes is accompanied by the normalization of lipofuscin levels in the brain and an increase in the steady-state levels of the mammalian autophagy marker microtubule-associate protein 1 light chain 3-II (LC3-II). We also find that DeltaQ-htt expression in vitro increases autophagosome synthesis and stimulates the Atg5-dependent clearance of truncated N-terminal htt aggregates. DeltaQ-htt's effect on autophagy most likely represents a gain-of-function, as overexpression of full-length wild-type htt in vitro does not increase autophagosome synthesis. Moreover, Hdh(DeltaQ/DeltaQ) mice live significantly longer than wild-type mice, suggesting that autophagy upregulation may be beneficial both in diseases caused by toxic intracellular aggregate-prone proteins and also as a lifespan extender in normal mammals.